Estimation of Time-Dependent Delay Models at Actuated Traffic Signals in Duhok City - Millet Salim Mohammed Doski; Aso Faiz Saeed Talabany (Zanco Journal of Pure and Applied Sciences, 2021)
Duhok City, developed rapidly in recent years, leading to an increase in the traffic volume on its streets which are not sufficient for this increase resulting in traffic congestion. Therefore, this paper studied the delay as an important measure of effectiveness at traffic signals. The delay was measured and predicted (for saturated and under saturated conditions) to help in solving some underestimation problems by using the transportation system management (TSM) techniques. Five signalized intersections on Barzani major street in Duhok city was chosen. Vehicle delay was measured in these intersections directly from field, then it was calculated using the time-dependent equations recommended by three different official manuals, Highway Capacity Manual (HCM2000), Canadian Capacity Guide (ITE1995) and Australian Capacity Guide (ARRB1995). After that comparisons between the results of each theoretical method and the field result was made. Finally, the regression analysis technique was used to establish different relationships between the delay data obtained from the field and each of the theoretical methods to find the best applicable model to predict the vehicle delay at signalized intersections in Duhok City. It was proved that the logarithmic relationship between field and theoretical results obtained from the Canadian Capacity Guide is the best